Mass Customisation: An Entrepreneurial Marketing Opportunity - Roy, Rajeev (Indian Journal of Marketing, 2006)
Examples of mass customization are on the rise throughout the world but there are not many significant such consumer offerings in India. This paper explores dimensions of marketing as practiced by small, entrepreneurial firms and explores the fit between those dimensions and characteristics important for the successful implementation of mass customization.This article does not just make a case for adoption of mass customization practices by entrepreneurial firms in India, but also tries to explore those dimensions of entrepreneurial marketing which would help the firms implement their mass customization strategy. The paper refers to recent academic literature on mass customization, entrepreneurship and entrepreneurial marketing as well as other related fields. This paper also refers to practices and strategies of many large and small firms which have implemented mass customization.